Comparison of the Metabolic and Behavioral Disturbances following Paraventricular- and Ventromedial-Hypothalamic Lesions - Chang, PengKwei (My University, 1985)
Lesions of the ventromedial hypothalamus (VMH) result in an obesity syndrome characterized by metabolic and behavioral disturbances. It has recently been indicated that damage to the paraventricular nucleus of the hypothalamus (PVH) also leads to changes characteristic of obesity. Although deficits following VMH lesions have been characterized extensively, less is known about the consequences of PVH damage. This thesis presents a series of experiments providing a detailed comparison of the two hypothalamic lesion syndromes.
Initially, to assess the basic features of the syndromes, rats underwent VMH, PVH, or sham lesions and were maintained ad libitum for 15 weeks on a series of test diets. Overall, lesion groups gained similar amounts of weight (significantly more than controls) and were equally hyperphagic. However, carcass analyses revealed that although both lesion groups had larger body fat compartments than controls, VMH rats were fatter than PVH animals. Similarly, although insulin levels in both lesion groups were elevated, only VMH rats had a significant hyperinsulinemia.
A defining feature of the VMH obesity is the development of certain disturbances of visceral secretion and excessive adipose stores even in the absence of hyperphagia. To assess whether the PVH obesity shares these characteristics, food intake of PVH and VMH rats were restricted postlesion to control body weights. First, gastric acid secretion was measured to index lesion-induced changes in visceral secretion. VMH rats developed a persisting hypersecretion immediately postlesion; acid secretion levels of PVH rats were normal. In a second experiment, PVH and VMH rats were maintained at control weights for 28 days postlesion by restricted feeding of either a standard pellet or high fat diet. In both diet conditions, VMH rats became obese but PVH rats did not.
Finally, the effects of PVH and VMH lesions on behavioral reactivity to orosensory properties of food were assessed by comparing the sham feeding responses of PVH, VMH and control rats to liquid diets varying in palatability. Control animals increased sham feeding with ascending sucrose concentrations. VMH animals showed disproportionately large increases in consumption with increased sucrose. PVH animals showed sham feeding changes similar to VMH rats.
These data indicate similar effects of PVH and VMH lesions on behavioral measures; specifically, in normal, and sham, feeding. However, these two lesions produce different effects on metabolic and secretion measures. It is concluded that the etiologies of the two obesity are fundamentally different.
Keywords: Psychology; Psychology